Trypanosomatid-Caused Conditions: State of the Art of Therapeutics and Potential Applications of Lipid-Based Nanocarriers - Muraca, Giuliana; Berti, Ignacio Rivero; Sbaraglini, María L.; Fávaro, Wagner J.; Durán, Nelson; Castro, Guillermo R.; Talevi, Alan (Frontiers in Chemistry, 2020)
Trypanosomatid-caused conditions (African trypanosomiasis, Chagas disease, and leishmaniasis) are neglected tropical infectious diseases that mainly affect socioeconomically vulnerable populations. The available therapeutics display substantial limitations, among them limited efficacy, safety issues, drug resistance, and, in some cases, inconvenient routes of administration, which made the scenarios with insufficient health infrastructure settings inconvenient. Pharmaceutical nanocarriers may provide solutions to some of these obstacles, improving the efficacy–safety balance and tolerability to therapeutic interventions. Here, we overview the state of the art of therapeutics for trypanosomatid-caused diseases (including approved drugs and drugs undergoing clinical trials) and the literature on nanolipid pharmaceutical carriers encapsulating approved and non-approved drugs for these diseases. Numerous studies have focused on the obtention and preclinical assessment of lipid nanocarriers, particularly those addressing the two currently most challenging trypanosomatid-caused diseases, Chagas disease, and leishmaniasis. In general, in vitro and in vivo studies suggest that delivering the drugs using such type of nanocarriers could improve the efficacy–safety balance, diminishing cytotoxicity and organ toxicity, especially in leishmaniasis. This constitutes a very relevant outcome, as it opens the possibility to extended treatment regimens and improved compliance. Despite these advances, last-generation nanosystems, such as targeted nanocarriers and hybrid systems, have still not been extensively explored in the field of trypanosomatid-caused conditions and represent promising opportunities for future developments. The potential use of nanotechnology in extended, well-tolerated drug regimens is particularly interesting in the light of recent descriptions of quiescent/dormant stages of Leishmania and Trypanosoma cruzi, which have been linked to therapeutic failure.